2022
DOI: 10.1039/d2tb00846g
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive electrochemical platform integrated with a 3D graphene aerogel for point-of-care testing for tumor markers

Abstract: Point-of-care testing (POCT) of tumor markers, such as alpha-fetoprotein (AFP) and carcinoembryonic antigen (CEA), can be used for the early diagnosis of cancer. In this paper, a highly sensitive electrochemical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… This can be further proved by IR spectral results. It is well established that strong characteristic IR absorption peaks of GO appear at 1730 cm –1 (ν CO ), 1620 cm –1 (ν O–H ), 1582 cm –1 (ν CC ), and 1143 cm –1 (ν COH ), respectively . In the IR spectra of rGO and 1 @rGO, the absorption peaks at 1582 cm –1 (ν CC ) and 1620 cm –1 (ν O–H ) are maintained, and the absorption peaks at 1730 cm –1 (ν CO ) and 1143 cm –1 (ν COH ) become weak.…”
Section: Resultsmentioning
confidence: 97%
“… This can be further proved by IR spectral results. It is well established that strong characteristic IR absorption peaks of GO appear at 1730 cm –1 (ν CO ), 1620 cm –1 (ν O–H ), 1582 cm –1 (ν CC ), and 1143 cm –1 (ν COH ), respectively . In the IR spectra of rGO and 1 @rGO, the absorption peaks at 1582 cm –1 (ν CC ) and 1620 cm –1 (ν O–H ) are maintained, and the absorption peaks at 1730 cm –1 (ν CO ) and 1143 cm –1 (ν COH ) become weak.…”
Section: Resultsmentioning
confidence: 97%
“…The limit of detection (LOD) is calculated as 0.419 pg mL –1 through the ratio of detection peak current to 3.3δ Table S2 displays the comparison of the method with other existing methods for electrochemical analysis of CEA, suggesting the satisfactory sensitivity of the method with a lower LOD. For each concentration of CEA, the electrochemical analysis has been repeated at least three times and the average value of relative standard deviations (RSDs) is only 3.68%, indicating good reproducibility of the method. Furthermore, experiments have been conducted to prove the specificity of the method by using other tumor-associated glycoprotein biomarkers (e.g., MUC1, AFP, PD-L1, and PDGF-BB) and 10% diluted serum containing complex amounts of glycosylated substances as the controls.…”
Section: Resultsmentioning
confidence: 97%
“…The results demonstrated that the composed sandwich-type immunoassay protocol performed suitable reproducibility, high sensitivity, good precision, and resistance. 1.0 × 10 −8 -1.0 × 10 −5 mg mL −1 7.9 pg mL −1 [134] Graphene aerogel microspheres Folic acid (FA) and octadecylamine (OA)-functionalized graphene aerogel microspheres (FA-GAM-OA)…”
Section: Antibodies-based Biosensormentioning
confidence: 99%
“…The 3D-GA was prepared via in situ chemical reduction of graphene oxide with Lascorbic acid and then dehydration by freeze-drying by Hu et al [134]. After the modification of the 3D-GA, they were be used for detecting various tumor markers in liquid samples via electrochemical impedance spectroscopy (EIS).…”
Section: Prostate Specific Antigenmentioning
confidence: 99%